Modeling the impact of internet broadband on e-government service using structural equation model - Pruekruedee,S. (Springer Verlag, 2015)
© Springer International Publishing Switzerland 2015. The aim of this study is to test the hypothesis whether the e-Government service is positively affected by the readiness of physical telecommunications infrastructure especially internet broadband and mobile broadband while negatively impacted by the inefficiency of bureaucratic system. It applies the structural equation model (SEM) with limited cross-sectional data of the Networked Readiness Index (NRI) from 140 countries. The style of the modelling is quite similar to the single-equation regression with the difference at the estimation method using latent variables. The results reveal that the e-Government service is ready to provide to people along with the readiness of the telecommunications infrastructure. Unfortunately, the service is pulled back and slowed down by the inefficiency in the bureaucratic system. It is a must for the government to improve the efficiency and incentives for staffs in related government agencies to make them proactive to catch up with updated situation among the competition in the digital world.